2009
DOI: 10.1111/j.1464-410x.2009.08648.x
|View full text |Cite
|
Sign up to set email alerts
|

Are prostate needle biopsies predictive of the laterality of significant cancer and positive surgical margins?

Abstract: analyses were used to determine which factors before and during LRP influenced the positive surgical margin status. RESULTSThere was only minor agreement between the laterality of positive needle biopsies and laterality of any cancer and significant cancer on final-specimen pathology ( κ = 0.135 and 0.151, respectively). This was irrespective of the number of needle cores obtained or final-specimen Gleason grade. Similarly, the laterality of dominant cancer on needle biopsy had only a minor agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…20 In our cohort, the incidence of bilateral disease at resection was lower (50.5%). The Gleason score, clinical stage, PSA, and number of biopsy cores were not markedly different compared to the studies from Frota and colleagues 19 and Gallina and colleagues. 20 This difference could be explained by our multi-institutionnal cohort.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…20 In our cohort, the incidence of bilateral disease at resection was lower (50.5%). The Gleason score, clinical stage, PSA, and number of biopsy cores were not markedly different compared to the studies from Frota and colleagues 19 and Gallina and colleagues. 20 This difference could be explained by our multi-institutionnal cohort.…”
Section: Discussioncontrasting
confidence: 63%
“…In regards to disease extension within the contralateral lobe, a laparoscopic series by Frota and colleagues showed that unilaterally positive biopsies correlated weakly with both prostate cancer and PSM localization. 19 They reported that 79% and 82% of prostates in which biopsies were only positive on the right and left lobe had bilateral disease, respectively. Similarly, a study by Gallina and colleagues of 321 consecutive low-risk patients with unilateral disease at biopsy showed that 60.7% had bilateral disease following RP.…”
Section: Discussionmentioning
confidence: 99%
“…Large series show that PSM range between 6 and 31% in the retropubic RP [16,17,18], 12.6-27% in the laparoscopic approach [9,10,19] and 13.5-15.2% in the robotic technique [15,20]. Also the employment of an NS or non-NS technique does not result in significant differences in PSM rates: 5.9-24% PSM in NS groups, 5.8-31% in non-NS groups [16,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Mouraviev et al 17 studied 1186 RP specimens from patients with clinically localized cancer to establish the relation between biopsy and final pathology with regard to laterality of cancer and found that biopsy predicted unilateral cancers accurately in only 19.2% cases. Frota et al, 18 from the Cleveland Clinic, studied the accuracy of preoperative biopsy in predicting the laterality of significant cancer. They reported only minor agreement between biopsy laterality and laterality on final pathology (κ = .135).…”
Section: Discussionmentioning
confidence: 99%
“…They reported only minor agreement between biopsy laterality and laterality on final pathology (κ = .135). 18 Yoon et al 19 evaluated 100 patients with unilateral disease on biopsy and found that 65% had contralateral lobe involvement on RP histology and 23% had a greater cancer on the RP specimen. This would be worth investigating in a future study, and we would recommend that all pathologists report HGPIN on biopsy whenever present.…”
Section: Discussionmentioning
confidence: 99%